Working with climate data and niche modeling: I. Creation of bioclimatic variables - Ramírez Villegas, Julián Armando; Bueno Cabrera, Aaron (International Center for Tropical Agriculture, 2009)
With the recent and rapid spread of ecological niche modeling (ENM) and geographic information systems (GIS), the need for a detailed dataset of environmental characterization has increased substantially. The creation of the WorldClim dataset (Hijmans et al., 2005, available at http://www.worldclim.org) is a considerable advance in terms of global environmental characterization as it provides high resolution (i.e. nearly 1 km) climatic surfaces derived from historical records from a number of weather stations across the globe. With this dataset, several analyses by means of GIS can be performed. WorldClim provides high resolution monthly maximum (tmax), minimum (tmin), and mean temperatures (tmean), and monthly precipitation (prec); and from those, a set of 19 bioclimatic variables can be derived (Busby, 1991). The maximum entropy algorithm (Maxent, Phillips et al., 2006) for species distributions modeling is one of the most accurate and globally used ecological niche models. Many modelers currently use the set of bioclimatic variables available at the WorldClim website when modeling a certain species geographic distribution using Maxent. This is a relatively easy task when the user works with current conditions (interpolations historical observed data, representative of 1950-2000 climates) since the bioclimatic variables needed for the analysis can be directly downloaded from the WorldClim website. However, often when working with future conditions (i.e. climate change), these 19 bioclimatic layers must be derived from the three basic climatic variables (i.e. tmin, tmax, prec) no matter the future climate pattern (i.e. global climate model [GCM]) that will be used in the analysis. In this document, we present a simple tutorial to generate the necessary environmental datasets (i.e. 19 bioclimatic variables) to be used as inputs for the Maxent software (any version), without using any complicated Arc-Info script (i.e. AML).